VP01 Methods Of Patient Involvement Now And Beyond 2020: A Case Study. (2019) - Livingstone, Heidi; Leng, Gillian; Thomas, Victoria
Abstract : Introduction: Involving patients and the public in the health technology assessment (HTA) has always been fundamental to NICE. To ensure the appropriate method of patient involvement remains relevant to the evolving types of HTA, NICE uses varying methods of involvement. These methods have been reviewed to ensure they remain current and relevant for HTA now and beyond 2020, and also to give guidance on the approaches that should form a standard baseline and those that could be optional. Methods: We identified and mapped the different methods of patient involvement used at NICE across five types of HTAs: diagnostics; medical technologies; medicines; ultra-orphan conditions; and surgical procedures. We looked at the varying methods of early engagement identifying similarities and differences, and considered the benefits and challenges of each. Results: The different methods of patient and public involvement include: lay members (generalist and topic expert) involved in decision making, individual patient input (written and oral), and patient group (organisation) input (written). The types of involvement fell into the following categories: written group submissions, written individual statements, surveys of individuals, pre-meeting events/workshops, oral testimonies at committees, and written consultation responses. The common methods across all HTA types were generalist lay members and consultations. Conclusions: This review highlighted the varying methods of involvement at NICE and highlighted additional methods that could be standardised across the different types of HTAs as a baseline. These included patient organisation submissions and a method for additionally including individual patients in each type of HTA. We identified that where patient involvement started early and continued at each stage of the process including a pre-meeting event, it was particularly helpful to the stakeholders' ability to contribute.